HYDRODYNAMIC ANALYSIS OF COMPOST SOIL MIXTURE AND ITS IMPLICATION ON GROWTH AND POTASSIUM UPTAKE IN CORNS (Zea Mays L) - Pambayun, W S Abisatya; Purwasasmita, Mubiar; Urahman, Taufik (MATTER: International Journal of Science and Technology, 2015)
The research has been conducted on the hydrodynamics analysis of compost soil mixture and its implications for growth and potassium uptake in corns. The study design arranged in a completely randomized method with six repetitions for soil treatment (T0), a mixture of soil:compost 3:1 (T1), and a mixture of soil:compost 1:1 (T2) also treatment without nutrients (N0), NPK with 200 kg/ha concentration (N1), and NPK with 400 kg/ha concentration. (N2). The research method was conducted on the porosity, capillarity and water holding test. The results showed soil:compost mix of 1:1 has a porosity value of 0.66±0.01 (11% greater than the porosity of the soil) and water holding value of 64.79±1.99 (18% greater than water holding of the soil). Corn plants grown in soil:compost mix of 1:1 has grown 35% higher than the planting of corn in soil and biomass gain of 125%. Potassium uptake in corn plants grown in compost soil mix 1:1 are 5% higher than the potassium uptake of corn plants grown in soil. This can be concluded that giving compost to the soil can improve the structure of soil and the flow of water from the soil to the plant as well as the implications for the growth and potassium uptake in plants.